2019
DOI: 10.1039/c9sc01460h
|View full text |Cite
|
Sign up to set email alerts
|

Sequence information transfer using covalent template-directed synthesis

Abstract: Kinetically inert ester bonds were used to attach monomers to a template, dictating the sequence of the polymer product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 51 publications
2
77
0
Order By: Relevance
“…Although rudimentary self‐replication behaviors have been demonstrated, most of the reported systems do not allow transfer of coded information sequences as achieved by nucleic acids . In these context, there was earlier this year two interesting examples of sequence information transfer using dynamic (Figure ) or covalent bonds between coded template and substrates. Yet, these examples were achieved with rather small information sequences ( i. e .…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…Although rudimentary self‐replication behaviors have been demonstrated, most of the reported systems do not allow transfer of coded information sequences as achieved by nucleic acids . In these context, there was earlier this year two interesting examples of sequence information transfer using dynamic (Figure ) or covalent bonds between coded template and substrates. Yet, these examples were achieved with rather small information sequences ( i. e .…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…4,5 Indeed, some very significant progress in devising a synthetic "information chemistry" has been made in recent years, notably with the development of sequence-specific polymerisation (i.e. sequence-writing) methodologies and mass-spectrometric sequencing techniques, [6][7][8] information-transfer protocols, [9][10][11] and the use of small "reader-molecules" to recognise and report copolymer sequence-information. [12][13][14][15] Using the latter technique, we recently showed that highly sequence-dependent 1 H NMR complexation shifts are produced in the spectra of copolyimides based on 1,4,5,8-naphthalene tetracarboxylic diimide (NDI) on complexation of an aromatic "probe" molecule such as pyrene or perylene.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Indeed, some very significant progress in devising a synthetic "information chemistry" has been made in recent years, notably with the development of sequence-specic polymerisation (i.e. sequence-writing) methodologies and mass-spectrometric sequencing techniques, [6][7][8] information-transfer protocols, [9][10][11] and the use of small "readermolecules" to recognise and report copolymer sequenceinformation. [12][13][14][15] Using the latter technique, we recently showed that highly sequence-dependent 1 H NMR complexation shis are produced in the spectra of copolyimides based on 1,4,5,8-naphthalene tetracarboxylic diimide (NDI) on complexation of an aromatic "probe" molecule such as pyrene or perylene.…”
Section: Introductionmentioning
confidence: 99%